(untitled) (Teología, 2020)
Spirituality as a “new” theological discipline was a hot topic in the early twentieth century, but its antecedents are as old as theology itself. With the institutionalization of the chair in 1931, the denomination “Spiritual Theology” became generalized and the development of treaties on the subject started to be written. Vatican II chose to emphasize the unity of theology and its spiritual dimension; this was also the direction that the great theologians of the twentieth century followed. What future is open to Spirituality in theological studies? This article takes up the major milestones of the past century and some significant contributions in the past two decades about the epistemological status of “Spiritual Theology,” the development of Studies in Spirituality and the methods of Spirituality Research.